Development and validation of IPM schedule for safflower and chickpea strip cropping system under rainfed conditions in Maharashtra - and SURENDER KUMAR SINGH, SAROJ SINGH*, G.Y. PARLEKAR (Indian Phytopathology, 2006)
Development and validation of IPM technology for safflower and chickpea strip cropping system (3:6) was done and compared with farmers’ practice under rainfed conditions in Maharashtra. The IPM module consisted of field sanitation, ploughing/harrowing and collection of stubbles, sowing of resistant/tolerant variety of safflower (cv. Bhima moderately tolerant to aphid), chickpea (cv. Vijay resistant to wilt), seed treatment with Trichoderma viride @ 5 g kg1 seed before sowing, mixing sorghum seeds of early maturing cv. S-3 or mauli @ 50 g ha-1 to act as live bird percehs for predators, installation of pheromone traps for Helicoverpa @ 5 ha-1 35 days after sowing and two sprays of neem seed kernel extract (NSKE) @ 5% with one spray of dimethoate @ 0.03% in between on the basis of ETL. The IPM module was found significantly superior, economically feasible and less expensive in reducing pest and disease incidence and obtaining higher monetary net returns and cost benefit ratio in comparison to farmers’ practice.